One Step Synthesis of Ternary Composite of GNS/CNT/MnO2 for the Applications of Electrochemical and Photocatalytic Studies. (2017) - Siddeswara, D.M.K.; Venkatesh, T.; Mahesh, K.R. Vishnu; Mylarappa, M.; Anantharaju, K.S.; Kumara, K.N. Shravana; Raghavendra, N.; Shivakumar, M.S.
Abstract: The current research was mainly focused on synthesizing the graphene nano sheets (GNS) and GNS/CNT/MnO2 composite. The GNS/CNT /MnO2 composite were characterized using X-ray Diffracto meter (XRD), Elemental composition and Surface morphology were examined using Energy Dispersive X-Ray (EDX) analysis and Scanning Electron Microscopy (SEM). Electrochemical activity of the GNS/CNT/MnO2 composites was investigated through cyclic voltammetry and electrochemical impedance spectroscopy. The composite was capable of delivering a high specific capacitance with excellent cycling stability. The GNS/CNT/MnO2 catalyst was also applied to degrade different nonvolatile compounds such as Methylene blue (MB) and Malachite green (MG). The performance of GNS/CNT/MnO2 showed rapid degradation of dyes of high concentration.